2015
DOI: 10.1039/c4tx00126e
|View full text |Cite
|
Sign up to set email alerts
|

A no observed adverse effect level for DNA adduct formation in rat liver with prolonged dosing of the hepatocarcinogen 2-acetylaminofluorene

Abstract: We have previously reported that the DNA-reactive hepatocarcinogen 2-acetylaminofluorene (AAF) produced in rat liver several key effects that were less than linear over a range of repeat doses, and that at low cumulative doses, no-adverse-effect-levels (NOAEL) were observed for several effects including hepatocellular cytotoxicity, enhanced cell proliferation, induction of preneoplastic foci and promotable liver neoplasms, although DNA adducts were still formed at dosages below the lowest NOAEL of 28 mg kg −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…One possible explanation is that the N -OH-2-AF-derived DNA adducts are more potent inducers of DNA strand breaks than the N -OH-2-AAF-derived DNA adducts, although dG-C8-AF is assumed to be the major adduct formed after treatment with both N -OH-2-AF and N -OH-2-AAF. However, 32 P-postlabelling does not allow direct structural identification of the DNA adducts formed ( 59 , 60 ) and 2-AAF has been shown to be capable of forming multiple adducts which can be labelled with different efficiency during 32 P-postlabelling ( 66 , 68 ). Differences in the short- and long-term persistence of 2-AAF-induced DNA adducts have been reported ( 64 , 68 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the N -OH-2-AF-derived DNA adducts are more potent inducers of DNA strand breaks than the N -OH-2-AAF-derived DNA adducts, although dG-C8-AF is assumed to be the major adduct formed after treatment with both N -OH-2-AF and N -OH-2-AAF. However, 32 P-postlabelling does not allow direct structural identification of the DNA adducts formed ( 59 , 60 ) and 2-AAF has been shown to be capable of forming multiple adducts which can be labelled with different efficiency during 32 P-postlabelling ( 66 , 68 ). Differences in the short- and long-term persistence of 2-AAF-induced DNA adducts have been reported ( 64 , 68 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rats exposed to low doses of two other genotoxic hepatocarcinogens contained in food, N -nitrosodiethylamine and 2-amino-3-methylimidazo[4,5- f ]quinoline, also showed the existence of different no-effect levels for different parameters relevant to carcinogenesis 70 , 73) . In addition, Williams et al 74 , 75) found NOAEL for DNA adduct formation in the livers of rats treated with low doses of the genotoxic hepatocarcinogen, 2-acetylaminofluorene. These studies concluded that a threshold, at least a practical threshold, exists for the carcinogenicity of genotoxic carcinogens, including direct mutagens.…”
Section: Quantitative Assessment Of Genotoxic Carcinogensmentioning
confidence: 99%
“…However, current research using rigorous approaches reveals no-effect levels for DNA-reactive carcinogens. [56][57][58] Nevertheless, the features of DNA-reactive carcinogens are indicative of a high degree of hazard to potentially exposed humans (see below) and it is probably for this reason that the majority of carcinogens recognized by the International Agency for Research on Cancer (IARC) 59 as having caused human cancer is of the DNA-reactive type (Table 2).…”
Section: Dna-reactive (Genotoxic) Carcinogensmentioning
confidence: 99%
“…The concepts of dose-effect relationships and thresholds are discussed in detail by Calabrese. 174 The most extensive investigations of thresholds have been in rat liver carcinogenesis where no-observed-adverse-effect-levels (NOAEL) have been documented for DNA adduct formation, 57 induced cell proliferation, 56 formation of preneoplastic lesions 56,175,176 and development of promotable neoplasms. 169 The accumulated data base supports the concept of thresholds for effects of DNA-reactive carcinogens.…”
Section: Human Risk Assessmentmentioning
confidence: 99%